Translating for the community - Taibi, Mustapha (Bristol, UK ; Blue Ridge Summit, PA : Multilingual Matters, 2018)
This book offers rich insights into the practice of community translation. Chapters outline the specific nature and challenges of community translation, quality standards, training and the relationship between community translation as a professional practice and volunteer or crowd-sourced translation.
Frontmatter -- Contents -- Contributors -- Acknowledgements -- Foreword -- Introduction / Taibi, Mustapha -- 1. Quality Assurance in Community Translation / Taibi, Mustapha -- 2. Education for Community Translation: Thirteen Key Ideas / Kelly, Dorothy -- 3. From the Classroom to the Job Market: Integrating Service-Learning and Community Translation in a Legal Translation Course / Acedo, Alicia Rueda -- 4. From Practice to Theory: Societal Factors as a Norm Governing Principle for Community Translation / Lesch, Harold -- 5. Volunteers and Public Service Translation / García, Ignacio -- 6. Community Translation in the UK: An Enquiry into Practice / Townsley, Brooke -- 7. Community Translation in Spanish Penitentiaries: A Coordinated Approach / Garcés, Carmen Valero / Gutiérrez, Lázaro -- 8. Community Translation in the Australian Context / Ko, Leong -- 9. Linguistic Diversity Among Swahili-Speakers: A Challenge for Translation in Australia / Burke, Jean -- Concluding Remarks / Taibi, Mustapha -- Index
JSTOR
Keywords: Public service interpreting; Translating and interpreting -- Social aspects; Intercultural communication; Interprétation communautaire (Traduction); Communication interculturelle; Migration, immigration & emigration; Sociolinguistics; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; LANGUAGE ARTS & DISCIPLINES -- Readers; LANGUAGE ARTS & DISCIPLINES -- Spelling; Intercultural communication; Public service interpreting; Translating and interpreting -- Social aspects; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting